1993
DOI: 10.2118/20383-pa
|View full text |Cite
|
Sign up to set email alerts
|

A General History Matching Algorithm for Three-Phase, Three-Dimensional Petroleum Reservoirs

Abstract: An algorithm is developed to estimate absolute permeability in multi-phase, multilayered petroleum reservoirs. Summary A numerical algorithm is developed to estimate absolute permeability in multi-phase, multilayered petroleum reservoirs permeability in multi-phase, multilayered petroleum reservoirs based upon noisy observation data, such as pressure, water cut, gas-oil ratio and rates of liquid and gas production from individual layers. A Chevron Black-Oil c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 28 publications
0
26
0
Order By: Relevance
“…We acknowledge the work of Oliver and Chen [2011] for part of this literature search. An overview of algorithms and applications can be found in Makhlouf et al [1993] and a more recent overview in the book from Oliver et al [2008].…”
Section: Literature Reviewmentioning
confidence: 99%
“…We acknowledge the work of Oliver and Chen [2011] for part of this literature search. An overview of algorithms and applications can be found in Makhlouf et al [1993] and a more recent overview in the book from Oliver et al [2008].…”
Section: Literature Reviewmentioning
confidence: 99%
“…where (Makhlouf et al, 1993) or variable metric method (Yang and Watson, 1988), we need only compute the gradient of the objective function and this can be done by setting β = O(m) in the adjoint procedure. In this case, one only needs to solve the adjoint system Eq.…”
Section: Adjoint Equationsmentioning
confidence: 99%
“…Here, we use the Polak-Ribière form of the nonlinear conjugate gradient algorithm; see Fletcher (1987). Makhlouf et al (1993) applied the conjugate gradient method to estimate 450 gridblock permeabilities by history matching production data obtained under multiphase flow conditions. In one example, 110 iterations were required to obtain conver-gence.…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1990s, the state-of-the-art in automatic history matching was probably best typified by the work of Makhlouf et al [114] who demonstrated a methodology capable of history matching synthetic data from two-and three-phase reservoirs (simulation grid and well locations are shown in Fig. 2a).…”
Section: Introductionmentioning
confidence: 99%
“…2a). In Makhlouf et al [114], the permeability distribution is modeled by bicubic spline function, an adjoint system was used to compute the gradient, and a conjugate gradient method was used to adjust the coefficient of the spline function of each simulation gridblock (450 parameters in total) for minimization of the data mismatch. In the key example, the squared data mismatch function for 10 years of simulated history, including 1,413 pressure data, 785 water cut and rate data, was reduced by a factor of 200 in approximately 200 iterations, requiring 11 cpu-hours on a Cray XMP-48 with four CPU.…”
Section: Introductionmentioning
confidence: 99%